Evaluation of The Implementation of IBM IOC Using the Delone and Mclean Model - dwi ita sari (Journal of Innovation and Applied Technology, 2021)
The success of information systems that can produce precise, accuracy, quality, and fast information that enhances the performance of organizations and people. According to Delone and McLean's model, there are an information system's critical success factors. Six key variables that support information systems success are information quality, quality system, service quality, use, user satisfaction, and net benefits. This research uses quantitative research methods, and the data used were 80 respondents by using purposive sampling, assisted by using questionnaire data collection methods. Analysis of the data used is PLS-SEM using the SmartPLS application. The results showed a significant effect on the quality information on use, user satisfaction, and net benefits. There is no significant effect on the quality system to use, user satisfaction, and net benefits. Quality of service is significant for use and net benefits, but there is no significant effect on user satisfaction.